A Stress Response Program at the Origin of Evolutionary Innovation in the Skin. (July 2019) - Eckhart, Leopold; Ehrlich, Florian; Tschachler, Erwin
The skin epithelium, ie, the epidermis, of dolphins and whales (cetaceans) is up to 50 times thicker than that of humans and other mammals living on land. Recently, comparative genomics revealed further striking differences in the cytoskeleton of the outer layers of the epidermis in aquatic and terrestrial mammals. Cetaceans lack the cytoskeletal keratins, which make up more than half of the total protein mass in the cornified epidermal layer of terrestrial mammals under homeostatic conditions. By contrast, orthologs of stress-inducible epithelial keratins are conserved in cetaceans and these keratins are constitutively expressed in their skin. Thus, the epidermal stress response program of a terrestrial common ancestor of modern mammals has become the default program of epidermal differentiation and a central component of the unique cutaneous organization of cetaceans. We propose that phenotypic plasticity during stress responses plays important roles in the evolution of the skin.